Cryptocurrency, Terrorism Financing, and the Dark Web: An Exploratory Study of the Role of Anonymous Transactions in Supporting Terrorist Activities - Oladipupo, AbdulMalik Olalekan (African Journal of Stability and Development (AJSD), 2025)
The expansion of cryptocurrency has reshaped financial systems by enabling decentralised transactions and new digital applications. However, its pseudonymity and global reach have also enabled ransomware, darknet trading, money laundering, and terrorism financing, creating challenges for regulators seeking to protect financial integrity. This study examines the intersection of cryptocurrency, cybercrime, and governance. It identifies techniques exploited by criminals, evaluates forensic and regulatory countermeasures, and considers the governance dilemmas posed by these developments. A qualitative, desk-based approach was adopted, drawing on peer-reviewed literature, institutional policy reports (FATF, IMF, Europol), and industry analyses (Chainalysis, Elliptic, TRM Labs). Thematic content analysis was used to trace patterns of illicit cryptocurrency use, enforcement actions, and regulatory innovations. The findings reveal that blockchain forensics and coordinated policy efforts have strengthened oversight. Yet criminals increasingly use privacy coins, decentralised finance protocols, mixers, and cross-chain laundering to bypass detection. Enforcement remains inconsistent, hindered by fragmented regulation and gaps in cross-border cooperation. Cryptocurrency-enabled crime and terrorism financing remain adaptive threats that test financial stability and governance frameworks. Stronger international coordination, harmonised regulation, and advanced forensic tools are essential to reduce risks. The study recommends deepening cross-border collaboration, investing in blockchain analytics, and adopting flexible governance models that balance innovation with accountability.